Media-IT Competences in Prospective Teachers - Wacław Strykowski; Justyna Strykowska-Nowakowska (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The article is designed as a proposal for contemporary teacher's competences. We start with the concept of competence, its characteristics and division into personal and professional human competences. After presenting professional competences according to Komitet Nauk Pedagogicznych PAN, we proceed to the media-IT competences as especially important for the professions of teaching and pedagogy. In the era of the society of knowledge and digitalization. The article also contains diagnostic and mainly qualitative research results, that was conducted among students, prospective teachers of humanistic subjects.